Prognostic Factors in Male Breast Cancer: A Retrospective Nationwide Study in South Korea by the Study of SMARTSHIP Group - Park, Sungmin; Hur, Ho; Lee, Ji Sung; Yoon, JaeSun; Hur, Sung Mo; Chung, Il Yong; Lee, Jong Won; Youn, Hyun Jo; Oh, Se Jeong; Lim, Cheol Wan; Lee, Jihyoun (Journal of breast cancer, 2021)
This study evaluated the incidence, the survival outcomes and its prognostic factors for male breast cancer (MBC) in Korea. Using the National Health Insurance Service database of Korea, we identified MBC patients who had the new claim code of C50. Medical records including type of surgeries and radiotherapy within one year of the first claim and death records were reviewed. Between 2005 and 2016, 838 newly diagnosed MBC patients were included (median follow-up, 1,769 days). The 70-74-year age group had the highest incidence of MBC. The 5-year survival rate was 73.7%. Age > 65 years, low income, no surgical intervention, no tamoxifen use, and > 2 comorbidities correlated with a worse outcome. MBC incidence has increased over time, and its peak is noted at age > 70 years. Age > 65 years, > 2 comorbidities, no surgical intervention, and no tamoxifen use correlate to poor prognosis.